2019
DOI: 10.1093/schbul/sbz078
|View full text |Cite
|
Sign up to set email alerts
|

Single Session Transcranial Magnetic Stimulation Ameliorates Hand Gesture Deficits in Schizophrenia

Abstract: Social interaction is impaired in schizophrenia, including the use of hand gestures, which is linked to poor social perception and outcome. Brain imaging suggests reduced neural activity in a left-lateralized frontoparietal network during gesture preparation; therefore, gesturing might be improved through facilitation of left hemispheric brain areas or via disruption of interhemispheric inhibition from the right homolog. This study tested whether repetitive transcranial magnetic stimulation (rTMS) protocols wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 44 publications
1
37
0
3
Order By: Relevance
“…Thus, cathodal stimulation of the left hemisphere and anodal stimulation of the right hemisphere leads to disadvantages in the delay-detection task for HC (see also, Straube et al , 2017 a ), but results in better performance in patients. It might be the case that results are affected by group differences in interhemispheric rivalry, which have been reported in repetitive transcranial magnetic stimulation studies for neglect ( Nyffeler et al , 2019 ), in gesture performance in healthy subjects ( Vanbellingen et al , 2020 ) and in schizophrenia ( Walther et al , 2020 ). Thus, stimulation of a brain area may inhibit the homologue of the other hemisphere (and vice versa).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, cathodal stimulation of the left hemisphere and anodal stimulation of the right hemisphere leads to disadvantages in the delay-detection task for HC (see also, Straube et al , 2017 a ), but results in better performance in patients. It might be the case that results are affected by group differences in interhemispheric rivalry, which have been reported in repetitive transcranial magnetic stimulation studies for neglect ( Nyffeler et al , 2019 ), in gesture performance in healthy subjects ( Vanbellingen et al , 2020 ) and in schizophrenia ( Walther et al , 2020 ). Thus, stimulation of a brain area may inhibit the homologue of the other hemisphere (and vice versa).…”
Section: Discussionmentioning
confidence: 98%
“…Social perception. The profile of nonverbal sensitivity (PONS) 31 is used to assess social perception, linked to social interaction, 23 using scenes with facial expressions, voice intonations, and/or bodily gestures. The test of upper limb apraxia (TULIA) 32 was used to assess the accuracy of performance of 48 hand gestures (meaningless, intransitive, or transitive), half of which are performed on demonstration of the experimenter (imitation), whereas the other half are performed following verbal instructions (pantomime).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Among 3 tDCS studies, two of which found significant effects only in emotion recognition, one of which targeted depression 25 and the other targeted schizophrenia, 22 as shown in Table 1. 23,24 used the same parameters among active and sham groups. "Significant effects in social perception" meant that stimulation enhanced the ability to assess the accuracy of performance of hand gestures.…”
Section: Effects Of Neuromodulation For Social Cognitive Deficitsmentioning
confidence: 99%
“…This suggests that pharmacological treatments may not be ideal candidates and offer no long-term solution in taming movement abnormalities. Preliminary findings suggest non-invasive brain stimulation (NIBS) is a potential candidate in alleviating movement abnormalities in schizophrenia patients ( Walther et al, 2020a , c ). Several ongoing clinical trials are currently administered to further assess the efficacy of NIBS ( Lefebvre et al, 2020 ); Personalized Non-invasive Neuromodulation by rTMS for Chronic and Treatment-Resistant Catatonia trial (RETONIC, NCT03116425), Overcoming Psychomotor Slowing in Psychosis trial (OCoPS-P, NCT03921450), and Brain Stimulation And Group Therapy to Improve Gesture and Social Skills in Psychosis trial (BrAGG-SoS, NCT04106427).…”
Section: Treatment Options For Movement Abnormalitiesmentioning
confidence: 99%